Rezolva ecuatia
3(x+5)-6=2(5x+1)-42
Răspunsuri la întrebare
Răspuns de
3
3(x+5)-6=2(5x+1)-42
3x+15-6=10x+2-42
3x+9=10x-40
3x-10x=-40-0
-7x=-49 deci x=7
3x+15-6=10x+2-42
3x+9=10x-40
3x-10x=-40-0
-7x=-49 deci x=7
Răspuns de
3
3(x+5)-6 = 2 (5x + 1) -42
3x + 15 - 6 = 10x+2 - 42
3x + 9 = 10x - 40
3x - 10x = -40 - 9
-7x = -49
x = 7
3x + 15 - 6 = 10x+2 - 42
3x + 9 = 10x - 40
3x - 10x = -40 - 9
-7x = -49
x = 7
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Fizică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă